Direitos humanos, alteridade e filosofia da libertação: a outra América Latina - LOBO, Lívia Teixeira Moura (Universidade Federal do Pará, 2023)
The basic idea of the thesis is to persist in the study of otherness as an ethical foundation of human rights, but now reflecting how normativity based on otherness can contribute fundamentally to human rights. In introduction the fragility of human rights is presented, either because they are a field of veiled ethical disputes that forge violence, as because they are a field in which conflict generates debate and, consequently, critical thinking. Latin America, as the Other, acts in this debate claiming an alterity that the law tends to cover up. The otherness makes demands that the law does not know. The first chapter is dedicated to a literature review about human rights, indicating the porosity of this language to a new criticism. The modern origin and the subject's promise of emancipation contrast with the oppression carried out through the liberal morality that permeates these rights. At the same time, it is a language so widespread that it seems wasteful to direct efforts to another area, where the means to act, to claim morally and politically are not known. The second chapter will confront Levinas' otherness, in which the Other is absolutely Other in its metaphysical exteriority that impels the freedom of the passive Self. Dussel presents an interpellant Other, which suggests, attacks, provokes, becomes aware of his neglected alterity and goes on to the praxis of liberation. There is an independent performance in the Other of the philosophy of liberation, he does not need approval, his helplessness is fruitful, criticism develops from the negativity of the current totality. The positive and critical-negative ethical principles are presented as that which requires, in the abstract, a normativity based on otherness. The last chapter proposes to consolidate the reach of the general objective, addressing the basic distinction of the philosophy of Dussel and Levinas, and the emergence of that of the analytical method so the Other leaps into critical reflection as the source of all ethical transformation - it is about a metaphysical moment and the return to totality. The Politics, which houses the law as an institution, subsumes the ethical principles in a similar way, informing human rights primarily about its formal aspect of legitimacy, about its role as a claim language in the face of system corruption and about the constitutive intersubjectivity of the system. subject that holds them back, making the predicate consensus of the symmetrical discursive participation of those who form the political community more solid.